Vimseltinib versus placebo for tenosynovial giant cell tumour (MOTION): a multicentre, randomised, double-blind, placebo-controlled, phase 3 trial - Gelderblom, Hans; Bhadri, Vivek; Stacchiotti, Silvia; Bauer, Sebastian; Wagner, Andrew J; van de Sande, Michiel; Bernthal, Nicholas M; López Pousa, Antonio; Razak, Albiruni Abdul; Italiano, Antoine; Ahmed, Mahbubl; Le Cesne, Axel; et al. (The Lancet (British edition), 2024)
Tenosynovial giant cell tumour (TGCT) is a locally aggressive neoplasm for which few systemic treatment options exist. This study evaluated the efficacy and safety of vimseltinib, an oral, switch-control, CSF1R inhibitor, in patients with symptomatic TGCT not amenable to surgery. MOTION is a multicentre, randomised, double-blind, placebo-controlled, phase 3 trial done in 35 specialised hospitals in 13 countries. Eligible patients were adults (aged ≥18 years) with a histologically confirmed diagnosis of TGCT for which surgical resection could potentially worsen functional limitation or cause severe morbidity. Patients were randomly assigned (2:1) with interactive response technology to vimseltinib (30 mg orally twice weekly) or placebo, administrated in 28-day cycles for 24 weeks. Patients and site personnel were masked to treatment assignment until week 25, unless progressive disease was confirmed earlier. The primary endpoint was objective response rate by independent radiological review using Response Evaluation Criteria in Solid Tumors, version 1.1 (RECIST) at week 25 in the intention-to-treat population. Safety was assessed in all patients who received the study drug. The trial is registered with ClinicalTrials.gov, NCT05059262, and enrolment is complete. Between Jan 21, 2022, and Feb 21, 2023, 123 patients were randomly assigned (83 to vimseltinib and 40 to placebo). 73 (59%) patients were female and 50 (41%) were male. Nine (11%) of 83 patients assigned to vimseltinib and five (13%) of 40 patients assigned to placebo discontinued treatment before week 25; one patient in the placebo group did not receive any study drug. Objective response rate per RECIST was 40% (33 of 83 patients) in the vimseltinib group vs 0% (none of 40) in the placebo group (difference 40% [95% CI 29–51]; p<0·0001). Most treatment-emergent adverse events (TEAEs) were grade 1 or 2; the only grade 3 or 4 TEAE that occurred in more than 5% of patients receiving vimseltinib was increased blood creatine phosphokinase (eight [10%] of 83). One patient in the vimseltinib group had a treatment-related serious TEAE of subcutaneous abscess. No evidence of cholestatic hepatotoxicity or drug-induced liver injury was noted. Vimseltinib produced a significant objective response rate and clinically meaningful functional and symptomatic improvement in patients with TGCT, providing an effective treatment option for these patients. Deciphera Pharmaceuticals.